The Influence of Confining Stresses on Rock Fragmentation, Thrust Force, and Penetration Energy in Sandstone Indentation Tests Using Disc Cutters - Gaofeng Wang; Ting Ren; Gaolei Zhu (Advances in Civil Engineering)
Hard rock Tunnel Boring Machines (TBMs) engaging disc cutters as cutting tools have been employed in considerable underground coal mines to accommodate the requirement of more stone drivage as operations are going deeper. This study conducted a set of disc cutter indentation tests to explore the influence of confining stresses on rock fragmentation, thrust force, and penetration energy on sandstone, which is commonly encountered in underground coal mines. The test results show that there exists a critical confining stress, under which the maximum thrust force and penetration energy keep increasing with confining stress mounting while the maximum thrust force and penetration energy will decrease or flatten if it is surpassed. By combining with previous studies and comparing the critical confining stress values to the rock mechanical properties’ values, the critical value is most likely to be of cohesion. For subsurface rock fragmentation, the Constant Cross Section (CCS) disc cutter indentation has denser cracks and their orientations are more lateral than those under the V shape one; the V shape disc cutter indentation is less sensitive to confining stresses, with no notable increase of crack number and crack reorientation with increasing confinement. Thus, the CCS disc cutter is more favorable than the V shape one from the perspective of rock fragmentation under confining stresses.